Antinociceptive effects of tramadol and acepromazine in cats - Steagall, Paulo V. M. [UNESP]; Taylor, Polly M.; Brondani, Juliana T. [UNESP]; Luna, Stélio Pacca Loureiro [UNESP]; Dixon, Michael J. (Elsevier B.V., 2008)
Effects of tramadol and acepromazine on pressure and thermal thresholds were examined in eight cats. After baseline measurements, subcutaneous (SC) tramadol 1 mg/kg, acepromazine 0.1 mg/kg, tramadol 1 mg/kg with acepromazine 0.1 mg/kg, or saline 0.3 ml were given. Serial measurements were made for 24 h. Mean thermal thresholds did not change significantly [analysis of variance (ANOVA)] from baseline. The maximum thermal threshold increase above baseline was 2.8 +/- 2.8 degrees C at 6 h (P > 0.05) after tramadol; it was above the 95% confidence interval (0) at 0.75, 3 and 6 h. Pressure thresholds increased above baseline from 0.25 to 2 h after acepromazine (P < 0.05) and from 0.5 to 3 h after the combination (P < 0.05), with a maximum increase of 132 +/- 156 mmHg 0.25 h after acepromazine and 197 129 mmHg 0.5 h after the combination. Pressure thresholds were above the 95% Cl from 0.25 to 2 h after acepromazine and from 0.5 to 3 h after the combination. SC tramadol at 1 mg/kg in cats had limited effect on thermal and pressure nociception, but this was enhanced by acepromazine. Acepromazine alone had pressure antinociceptive effects. (c) 2007 ESFM and AAFR Published by Elsevier Ltd. All rights reserved.